Embedded, added, cocreated: Revisiting the value of information in an age of data. (8th December 2017) - Foster, Jonathan; Clough, Paul
Abstract : This article proposes that the value of information is a topic worth revisiting in the contemporary era. Although the topic has been of perennial interest to information professionals and others, since at the least the early 1980s, we believe that it is timely to revisit this question in the context of a more connected and networked environment of data, information, and knowledge. The principal argument is that existing models of information exchange and use do not sufficiently take account of the multiplicity of networked users as a source of value, for example, their implicit and explicit interactions with other users, and with the information system. We briefly review existing kinds of value that have been theorized, operationalized, and measured in the information science literature. Principally, these are the notions of information as embedded value; and information and information systems as adding value. To these notions we add the further notion of connected or cocreated value. We conclude our opinion article with a set of questions intended to orient future research into the question of the value of information in the contemporary era.